Molecular Technology In Maize (zea mays l.) Breeding To Be Applied The Agroforestry System - Ramlah Ramlah (Fakultas Pertanian Universitas Muara Bungo, 2023)
Maize is a versatile food source adaptable in tropical and subtropical regions. Efforts to optimize corn production and quality in supporting food security. Agroforestry is the integration of crop cultivation that combines tree and shrub species into agricultural systems to create environmental, economic, and social benefits. Optimization of the plant breeding program is an effort to obtain corn varieties that have specific characteristics that are desired and needed by farmers. The use of molecular marker technology is a method that is currently widely used and is proven to help the efficiency of specific gene introgression. Molecular markers can be used as a tool for plant selection with better accuracy, accuracy, and specificity. Molecular marker technologies vary in implementation for data collection, both technical and target data levels desired, depending on the ease of deployment, available human resources, facilities, and funding. Molecular markers used for maize are RFLP, RAPD, AFLP, STS, SCARs, SSR, ISSR, Transposons, and SNPs.